2009
DOI: 10.1161/circresaha.108.192179
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10 Inhibits Viral Replication Through Recruitment of Natural Killer Cells in Coxsackievirus B3-Induced Myocarditis

Abstract: Abstract-Coxsackievirus (CV)B3 is the primary cause of viral myocarditis. We previously observed CXC chemokine ligand 10 (CXCL10) upregulation in the myocardium early in infection. However, the impact of CXCL10 in CVB3-induced myocarditis is unknown. Using isolated primary mouse cardiomyocytes we demonstrated for the first time that cardiomyocytes can express CXCL10 on interferon-␥ stimulation. To explore the role of CXCL10 in CVB3-induced myocarditis, both CXCL10 transgenic and knockout mice were used. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 35 publications
3
67
3
Order By: Relevance
“…Viral titers were determined as described previously. 58 Briefly, HeLa cells were seeded into 6-well plates (8 × 10 5 cells per well) and incubated at 37°C for 20 h to a confluence of~0%, then washed with PBS and overlaid with 500 μl of virus serially diluted in cell culture medium. Virus was obtained by centrifugation (4000 × g) of freeze-thawed cell suspensions as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Viral titers were determined as described previously. 58 Briefly, HeLa cells were seeded into 6-well plates (8 × 10 5 cells per well) and incubated at 37°C for 20 h to a confluence of~0%, then washed with PBS and overlaid with 500 μl of virus serially diluted in cell culture medium. Virus was obtained by centrifugation (4000 × g) of freeze-thawed cell suspensions as described above.…”
Section: Methodsmentioning
confidence: 99%
“…These data strongly suggest a protective role for type I IFN, particularly IFNb, during coxsackieviral infection. Recently, the constitutive expression of CXCL10 in the heart has been shown to attract NK cells to the heart, reducing overall viral replication (12). Though much progress has been made, there is still a need to account for differential susceptibility to viral myocarditis among otherwise normal individuals due to natural variation.…”
mentioning
confidence: 99%
“…By interacting with its receptor CXCR3, CXCL10 manipulates natural killer cell trafficking and their production of IFN-. Yuan et al recently found CXCL10 levels in the heart to be inversely related to viral titers after coxsackievirus B3 infection and a massive infiltration of CXCR3 + , CD4 + , and CD8 + cells (Yuan et al 2009). The production of associated inflammatory cytokines followed with the infiltration of leukocytes though the anti-viral response was not effective in clearing the virus or ensuring survival in coxsackievirus B3-infected CXCL10 transgenic mice (Yuan et al 2009).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Yuan et al recently found CXCL10 levels in the heart to be inversely related to viral titers after coxsackievirus B3 infection and a massive infiltration of CXCR3 + , CD4 + , and CD8 + cells (Yuan et al 2009). The production of associated inflammatory cytokines followed with the infiltration of leukocytes though the anti-viral response was not effective in clearing the virus or ensuring survival in coxsackievirus B3-infected CXCL10 transgenic mice (Yuan et al 2009). CXCL10 did assist viral clearance and protect myocytes from damage in the early stages of infection by robustly attracting NK cells and enhancing IFN-production to infection sites (Yuan et al 2009).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation